2007
DOI: 10.1007/s10096-007-0285-5
|View full text |Cite
|
Sign up to set email alerts
|

Q fever osteoarticular infection: four new cases and a review of the literature

Abstract: Q fever is a worldwide-occurring zoonosis caused by Coxiella burnetii. Better knowledge of the disease and of evolving diagnostics can enable recognition of unusual manifestations. Reported here are four cases of Q fever osteoarticular infections in adults: two cases of Q fever tenosynovitis, which represent the first two reports of this infection, and two cases of Q fever spondylodiscitis complicated by paravertebral abscess. In addition, the literature is reviewed on the 15 previously reported cases of Q fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 26 publications
1
50
0
4
Order By: Relevance
“…6,7 Because of its nonspecific clinical presentation, chronic Q fever is probably underestimated, and the majority of patients experience symptoms for a lengthy period before diagnosis. 3 The range of osseous involvement is broad, from long to short bones. Single or multifocal involvement, with or without focal abscess collection, and sometimes multiple subcutaneous abscesses and fistulas have been described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Because of its nonspecific clinical presentation, chronic Q fever is probably underestimated, and the majority of patients experience symptoms for a lengthy period before diagnosis. 3 The range of osseous involvement is broad, from long to short bones. Single or multifocal involvement, with or without focal abscess collection, and sometimes multiple subcutaneous abscesses and fistulas have been described.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Indeed in our patients the mild inflammatory markers and the unspecific clinical complaints, added to the low suspicion rate, deferred diagnosis. Also, in case 1 there was involvement of metaphysis and epiphysis, with growth plate commitment, and in case 2, there was a huge 2 This trend can be attributed, in part, to changes in vaccine formulation, 3 evolution of the bacteria, 4 and improved laboratory testing. Polymerase chain reaction (PCR) is commonly used to test for pertussis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Pediatric cases received variable regimens of intracellularly active agents including rifampicin, trimethoprim sulfamethoxazole, ciprofloxacin, and linezolid, as well as doxycycline and hydrochloroquine. 8 A review of the limited number of reported Q fever osteoarticular infections advised combination treatment of at least 18 months, along with serological follow-up. 8 Despite these prolonged antibiotic courses, treatment failures have been reported.…”
Section: Figurementioning
confidence: 99%
“…8 A review of the limited number of reported Q fever osteoarticular infections advised combination treatment of at least 18 months, along with serological follow-up. 8 Despite these prolonged antibiotic courses, treatment failures have been reported. 6 Given the lack of proven efficacy, the potential for significant side effects associated with prolonged antibiotic treatment, and the lack of symptoms in an otherwise well child, a decision was made to continue close observation without initiating antimicrobial therapy.…”
Section: Figurementioning
confidence: 99%